2007
DOI: 10.1007/s11099-007-0009-1
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic responses of apricot (Prunus armeniaca L.) to photosynthetic photon flux density, leaf temperature, and CO<sub>2</sub> concentration

Abstract: Two cultivars (Katy and Erhuacao) of apricot (Prunus armeniaca L.) were evaluated under open-field and solar-heated greenhouse conditions in northwest China, to determine the effect of photosynthetic photon flux density (PPFD), leaf temperature, and CO 2 concentration on the net photosynthetic rate (P N ). In greenhouse, Katy registered 28.3 μmol m -2 s -1 for compensation irradiance and 823 μmol m -2 s -1 for saturation irradiance, which were 73 and 117 % of those required by Erhuacao, respectively. The optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The higher SD and SI could have given rise to a higher intercellular CO 2 which could explain the higher P max . This phenomenon was similar to that observed by Wang et al (2007a) for apricot, where the cultivars exhibited different adaptation abilities to low irradiance probably due to the genetic background effect.…”
Section: Parameterssupporting
confidence: 88%
“…The higher SD and SI could have given rise to a higher intercellular CO 2 which could explain the higher P max . This phenomenon was similar to that observed by Wang et al (2007a) for apricot, where the cultivars exhibited different adaptation abilities to low irradiance probably due to the genetic background effect.…”
Section: Parameterssupporting
confidence: 88%
“…For sun leaves, high aerosol loading resulted in a rapid decline in PAR received by the leaf surface, thereby reducing T leaf (Figure 6a,c). Previous works suggested that stomata have a slow response to environmental stimuli when leaf temperature is between 35 and 50°C (Ameye et al., 2012; Wang et al., 2007; Weston & Bauerle, 2007). In our study, we found that when the temperature was higher than 35.5℃, sun leaf photosynthesis began to decline (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The most reported phenomenon induced by high CO 2 is an increase in the photosynthetic carbon fixation rates. Plant growth and development are intensely affected by photosynthesis, with the carbon assimilates necessary for yield production ultimately produced via photosynthesis (Wang et al, 2007). Thus, a rise in the photosynthetic rate increases plant growth and development through an increment in carbohydrates production and in the water use efficiency (WUE) (Chaves, 1994).…”
mentioning
confidence: 99%